Impact of the COVID-19 Outbreak on the Behavior of Families in Italy: A Focus on Children and Adolescents - Uccella, Sara; De Grandis, Elisa; De Carli, Fabrizio; D'Apruzzo, Maria; Siri, Laura; Preiti, Deborah; Di Profio, Sonia; Rebora, Serena; Cimellaro, Paola; Biolcati Rinaldi, Alessandra; Venturino, Cristina; Petralia, Paolo; et al. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has changed individuals’ lifestyles to a great extent, particularly in Italy. Although many concerns about it have been highlighted, its impact on children and adolescents has scarcely been examined. The purpose of this study was to explore behavioral consequences and coping strategies related to the pandemic among families in Italy, by focusing on developmental ages from the caregivers’ perspective, three weeks into quarantine. An exploratory cross-sectional online survey was conducted over 14days. Google Forms was employed to conduct the survey. Demographic variables and pre-existing Psychological Weaknesses(PsW)were asked. Adults’ sleep difficulties (SleepScore) and coping strategies during quarantine were assessed. Behavioral changes related to quarantine of both subjects completing the form(COVIDStress) and their children (when present) were questioned. Of the 6,871 respondents, we selected 6,800 valid questionnaires; 3,245 declared children aged under 18 years of age(caregivers). PsWs were recognizable in64.9% among non-caregivers and in 61.5% of caregivers, with a mean PsW score of 1.42±1.26 and 1.30±1.25 over 3 points, respectively. The95.5% of the non-caregivers and the96.5% of caregivers presented behavioral changes with a mean COVIDStress of 3.85±1.82 and 4.09±1.79 over 8 respectivel(p<0.001). Sleep difficulties were present in the61.6% of the non-caregivers and in the 64.4% of the caregivers (p<0.001), who showed higher SleepScores (2.41±1.26 against 2.57±1.38 points over 6, p<0.001). COVIDStress (and SleepScore) strongly correlated with PsW (p<0.001). Caregivers observed behavioral changes in their children in the64,3% of the <6 years old and in72,5% of 6–18 years old. Caregivers’ discomfort related to quarantine (COVIDStress, SleepScore) was strongly associated to behavioral changes in both age groups of <6 and 6–18(p<0.001). Presence of caregivers’ coping strategies was less associated to behavioral changes in the <6 sample (p=0.001) but not in the 6–18(p=0.06). The COVID-19 pandemic has adversely impacted families in Italy with regard to behavioral changes, especially in high-risk categories with PsWs and caregivers, especially the ones with children aged <6 years. While coping strategies functioned as protective factors, a wide array of stress symptoms had implications for children’s and adolescents’ behaviors. It is recommended that public children welfare strategies be implemented, especially for higher-psychosocial-risk categories.